Physical and physiological demands and hormonal responses in basketball small-sided games with different tactical tasks and training regimes - Sansone, P.; Tessitore, A.; Paulauskas, H.; Lukonaitiene, I.; Tschan, H.; Pliauga, V.; Conte, D. (Journal of Science and Medicine in Sport, 2019)
Objectives: To evaluate external and internal training load (TL) and hormonal responses in basketball 3-versus-3 small-sided games (SSGs). Design: Randomized repeated-measures study. Methods Twelve male basketball players participated to four 3-versus-3 SSGs characterized by different tactical tasks (offensive; defensive) and training regimes (long-intermittent: three 4-min bouts with 2' rest in between; short-intermittent: six 2-min bouts with 1' rest in between). Variables measured were: PlayerLoad (PL); percentage of maximal heart rate (%HRmax); Edwards` TL. Before and after the SSGs, saliva samples were collected to measure cortisol (C) and testosterone (T). Two-way (task; regime) repeated-measures ANOVA was performed for PL and %HRmax; C concentrations were analysed with a three-way (task; regime; time: pre/post) repeated-measures ANOVA; non-parametric analyses were performed for Edwards` TL and T. Results: PL was moderately higher in offensive task (148.0 ± 16.8 AU) compared to defensive (137.1 ± 15.5 AU), and short regime (147.0 ± 18.2 AU) compared to long (137.9 ± 14.6 AU). %HRmax was moderately higher in offensive task (91.1 ± 4.1%) compared to defensive: (88.7 ± 5.4%), while it did not differ between regimes (long: 90.0 ± 5.6%) (short: 89.8 ± 4.2%); additionally, an interaction (task*regime) effect was found (ES: strong). Edwards` TL was moderately higher in offense-long SSG (56.6 + 2.4 AU) compared to defense-short (52.4 + 4.4 AU). C increased after the SSGs (ES: strong). T decreased after offense-short (ES: moderate) and increased after defense-long (ES: moderate) SSGs. Conclusions: Tactical tasks and training regimes influence external and internal demands of basketball SSGs. Steroid hormones respond in SSGs.